Evaluating choroidal vascular changes in young adults with high myopia utilizing swept source optical coherence tomography angiography - Qing wang; Lin-Bo He; Sha Li; Hong-Ling Liu; Yong Liu (Photodiagnosis and Photodynamic Therapy)
Purpose: Utilizing Swept source optical coherence tomography angiography (SS-OCTA) investigates the changes in the vascular characteristics of the choriocapillaris and larger vascular layers, including Sattler's and Haller's layers, in the macular region of young myopia patients, in order to Enhance our comprehension of the underlying mechanisms of the pathogenesis of myopia. Methods: A retrospective analysis was performed on 103 young adults (154 eyes) that underwent SS-OCTA. Axial lengths (AL) were measured, 64 eyes with AL < 26.5 mm as non-high myopia (NHM) and 90 eyes with AL ≥ 26.5 mm as high myopia (HM). Macular superficial capillary plexuses (SCP), deep capillary plexuses (DCP), choriocapillaris (CC) density, choroidal Sattler's and Haller's layers (CSHL) density, foveal avascular zone area (FAZ area), and subfoveal choroidal thickness (SFCT) were assessed. Multivariate regression analysis was employed to assess the effect of age,spherical equivalent(SE), axial length(AL),and SFCT on OCTA parameters. Results: SCP and DCP densities in the foveal retina of NHM group were significantly lower than those in HM group(SCP 20.09 ± 4.30 vs. 21.54 ± 4.52, p = 0.043;DCP14.73 ± 3.93 vs. 16.21 ± 4.07, p = 0.024). Also, CC density subfoveal was significantly lower in NHM group compared to HM group(55.02 ± 2.39 vs. 56.37 ± 2.76, p = 0.0001); CSHL density subfoveal and parafoveal temporal were also significantly lower in NHM than HM(subfoveal 55.78 ± 4.67 vs. 58.17 ± 4.41, p = 0.002;parafoveal temporal 52.10 ± 3.48 vs. 54.06 ± 4.12, p = 0.002). In the multiple linear regression analysis, density of SCP in the foveal retina was increased with higher myopia(sβ=0.226, p = 0.047)and decreased with aging(sβ=-0.304, p = 0.001). Moreover, gradual decrease of the DCP was observed with aging(sβ=-0.227, p = 0.004). CSHL density subfoveal increased with the increase in AL(sβ=0.318, p = 0.007). Conclusion: Age primarily influenced retinal vessel density, whereas axial length significantly affected Sattler's and Haller's layers. This also indicates that the subfoveal and parafoveal temporal CSHL densities are crucial for monitoring changes during myopia progression. Additionally, there appears to be a compensatory mechanism for high myopia to sustain visual function.